Problem-Based Learning Model According to Matthew 14:13-21 - Semi Ndolu; Ezra Tari (Jurnal Pendidikan Agama Kristen (JUPAK), 2022)
The problem of mastering learning materials is a teacher's struggle. The selection of the correct method can affect good learning outcomes. However, the learning method does not affect students' mastery of the material. This paper will review the PBL method in the gospel of Matthew 14:21. That is, the reader can see the technique of Jesus in providing a learning process for the disciples. The method used is descriptive qualitative. The writer found that the students were able to identify the problem. The problem the students found was a lack of food. So the solution offered by students is to buy food in the city. However, another problem that arises is the availability of budget and food. However, Jesus asked what they had. There were only five loaves of bread and two fish. Jesus showed that even though the potential is minimal, it will achieve the desired goal if maximised. The students are studying in a problematic situation; there is still a way out. After the learning was evaluated, it was found that the students were successful in the learning process.